Stakeholder Pressures and Decarbonization Strategies in Mittelstand Firms - Jörn H. Block; Pramodita Sharma; Lena Benz (Journal of Business Ethics, 2023)
This study examines the influence of stakeholder pressures and family ownership on strategic decarbonization choices of German Mittelstand firms. It distinguishes between symbolic strategies focusing on compensating CO2-emissions and substantive strategies directed toward reducing carbon emissions. The relative pressure exerted by internal and external stakeholders on these strategic choices is examined. Data from 443 manufacturing firms reveal that overall stakeholder pressures increase the pursuit of decarbonization strategies. Internal stakeholders pressures are associated with increased reliance on substantive decarbonization strategies both in family-owned and non-family-owned firms. Pressure from external stakeholders are associated with increased reliance on both substantive and symbolic decarbonization strategies only in non-family-owned firms. No effect of external pressures was found in family-owned firms. Implications for theory, management practice, and policy makers are discussed.
Keywords: 300; Decarbonization strategies; Family firms; Mittelstand; Stakeholder pressures; Symbolic and substantive strategies